Effectiveness of Psychoeducation on Burden among Family Caregivers of Adults with Schizophrenia: A Systematic Review and Meta-Analysis - Akunna Jane Okafor; Mark Monahan (Nursing Research and Practice, 2023)
Caring for relatives living with schizophrenia could lead to caregivers’ burden. It is believed that lack of information and understanding about schizophrenia and lack of skills to cope effectively while caring for their adult relatives largely contribute to the burden they experience. The burden is assessed using assessment scales. This review aims to assess the effectiveness of psychoeducation in alleviating the burden experienced by family caregivers of adults living with schizophrenia and to identify essential factors that facilitate positive outcomes. Five databases (ASSIA, CINAHL, Embase, MEDLINE EBSCO, and PsycINFO) were systematically searched using combinations of the following key terms: “family caregivers,” “schizophrenia,” “burden,” “psychoeducation,” and “adults.” Meta-analysis of included studies was conducted using RevMan 5.4. Five RCTs with 320 family caregivers were included in the review. Overall, none of the studies showed a low risk of bias. The evidence suggests that face-to-face group psychoeducation reduced family caregivers’ burden when measured across different time points: one-week postintervention (mean difference −3.87 and Cl −6.06 to −1.70), six months (MD −8.76 and Cl −12.38 to −5.13), and twelve months (MD −7.38 and Cl −9.85 to −4.91). Measurements immediately after the intervention, one month, and three months postintervention when reported narratively also showed a reduction in family caregivers’ burden. Face-to-face group psychoeducation provided for family caregivers effectively alleviates the burden they experience. Factors such as program content and teaching methods facilitated positive outcomes. It is recommended that psychoeducation should be integrated as a routine intervention for family caregivers.